Factors limiting glaucoma care among glaucoma patients in Nigeria: A scoping review. - Osamudiamen Cyril Obasuyi; Olabisi Olayemi Yeye-Agba; Oghenevwaire Joyce Ofuadarho (PLOS Global Public Health)
Glaucoma currently accounts for 11% of irreversible visual loss worldwide. Due to many factors, patients do not access the glaucoma care pathway and present late with poor vision, while many are undiagnosed or untreated. These factors may be personal-level dispositions or Institutional-level dispositions, limiting the awareness, diagnosis, and treatment of glaucoma or adherence to medications or follow-up clinic visits. This scoping review followed the JBI methodology for scoping reviews and was pre-registered on the open science platform (https://osf.io/wqx57/?view_only=727eb6c803764509a2809e5d0794e214). The PUBMED, EMBASE, WEB OF SCIENCE, AJOL, and GOOGLE SCHOLAR databases were systematically searched for studies published in English between 1990 and June 2023. Data were extracted and analysed along a conceptualised framework of factors limiting access to glaucoma care in Nigeria. Of the 336 records retrieved, 13 studies were included in this scoping review. These included one (1) mixed method (quantitative/qualitative) study, three qualitative studies, and nine quantitative studies spanning 2008-2022 covering eight states and 2,643 sampled respondents. Nine studies reported personal-level dispositions limiting glaucoma care, including low levels of education, unemployment, gender, living distance from the hospital, cost of care, and faith/religion. Four reported institutional-level dispositions, including the lack of proper equipment and expertise to diagnose or manage glaucoma. The factors limiting Glaucoma care in Nigeria are varied and may act alone or combined with other elements to determine the awareness or knowledge of glaucoma, uptake of glaucoma surgery, medication adherence, or clinic follow-up. While most of these factors limiting glaucoma care in Nigeria may be amenable to policy, a bottom-up approach is needed to improve the community's awareness and uptake of glaucoma services. A shift from the over-dependence and reliance on tertiary hospitals, which are often far away from the people who need them, is required to bridge the information and service gap currently being witnessed.